Leukocyte Integrin Antagonists as a Novel Option to Treat Dry Age-Related Macular Degeneration - Baiula, Monica; Caligiana, Alberto; Bedini, Andrea; Zhao, Junwei; Santino, Federica; Cirillo, Martina; Gentilucci, Luca; Giacomini, Daria; Spampinato, Santi (Frontiers in Pharmacology, 2021)
Age-related macular degeneration (AMD) is a complex multifactorial degenerative disease that leads to irreversible blindness. AMD affects the macula, the central part of the retina responsible for sharp central vision. Retinal pigment epithelium (RPE) is the main cellular type affected in dry AMD. RPE cells form a monolayer between the choroid and the neuroretina and are in close functional relationship with photoreceptors; moreover, RPE cells are part of the blood retina barrier that is disrupted in ocular diseases such as AMD. During ocular inflammation lymphocytes and macrophages are recruited, contact RPE and produce pro-inflammatory cytokines, which play an important role in AMD pathogenesis. The interaction between RPE and immune cells is mediated by leukocyte integrins, heterodimeric transmembrane receptors, and adhesion molecules, including VCAM-1 and ICAM-1. Within this frame, this study aimed to characterize RPE-leukocytes interaction and to investigate any potentially beneficial effects induced by integrin antagonists (DS-70, MN27 and SR714), developed in previous studies. ARPE-19 cells were co-cultured for different incubation times with Jurkat cells and apoptosis and necrosis levels were analyzed by flow cytometry. Moreover, we measured the mRNA levels of the pro-inflammatory cytokine IL-1β and the expression of adhesion molecules VCAM-1 and ICAM-1. We found that RPE-lymphocyte interaction increased apoptosis and necrosis levels in RPE cells and the expression of IL-1β. This interaction was mediated by the binding of α4β1 and αLβ2 integrins to VCAM-1 and ICAM-1, respectively. The blockade of RPE-lymphocyte interaction with blocking antibodies highlighted the pivotal role played by integrins. Therefore, α4β1 and αLβ2 integrin antagonists were employed to disrupt RPE-lymphocyte crosstalk. Small molecule integrin antagonists proved to be effective in reducing RPE cell death and expression of IL-1β, demonstrating that integrin antagonists could protect RPE cells from detrimental effects induced by the interaction with immune cells recruited to the retina. Overall, the leukocyte integrin antagonists employed in the present study may represent a novel opportunity to develop new drugs to fight dry AMD.